Performance Analysis of Load Balancing Techniques in Cloud Computing Environment - Raviteja Kanakala; V.Krishna Reddy (Institute of Advanced Engineering and Science, 2015)
Cloud computing is a forerunner among the technologies emerging today in the IT world. It has already been some years after the emergence of cloud technology but still the world didn’t get the complete fruits of cloud computing. Out of the many revolutionary results expected as outcomes from the cloud computing technology there were very few achieved and the rest of the expected are still under research. Two of the main obstacles in the usage of cloud computing are Cloud Security and Performance stability. Load Balancing is one of the elements that shows impact on the performance stability of cloud computing. In this paper we discuss about load balancing and different algorithms that are proposed for distributing the load among the nodes and also the parameters that are taken into account for calculating the best algorithm to balance the load. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7237